A Robust Page Ranking Method basedon Link-Visits of Web Page (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
Search engines generally return a large number of pages in response to user queries. To assist the users to navigate in the result list, ranking methods are applied on the search results. Web search engines encounter many new challenges with the increased amount of information on the web. Web documents have been a main resource for various purposes, and people rely on search engines to retrieve the desired documents. This paper proposes a dynamic and efficient Page rank algorithm for search engines to return quality results by scoring the relevance of web documents. The modified Page rank algorithm increases the degree of relevance than the original one, and decreases the time and efforts to find the desired documents from the set of results returned by search engine. Here, a page ranking mechanism called PRLV (Page Ranking based on Link Visits)is being devised for search engines, which works on the basic ranking algorithm of Google i.e. Page Rank and takes number of visits of inbound links of Web pages into account. To make rank value of pages dynamic rather than static, a new concept called PRLV is proposed and described, which takes into account users’ behaviour i.e. Link Visit Information, and calculates importance of pages.
Keywords: Search Engine; Page Rank Algorithm; PRLV